Rapidly Fatal Internal Carotid Artery Mycotic Aneurysm Rupture in a Rheumatoid Patient Taking a TNF-α Inhibitor: Case Report and Literature Review - Bowers, Christian A.; Saad, Dany; Clegg, Daniel O.; Ng, Perry; Clayton, Frederic; Haydoura, Souha; Schmidt, Richard H. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Object Tumor necrosis factor (TNF)-α inhibitors are effective at treating certain inflammatory and autoimmune disorders. They are generally safe; potential adverse events include infections (bacterial, fungal, and viral), congestive heart failure exacerbations, and the potential for demyelinating diseases and possibly certain malignancies. We present the first documented case of fungal internal carotid artery (ICA) mycotic aneurysm in a patient being treated with a TNF-α inhibitor. We also review the literature on infections with TNF-α inhibition and the management of previously reported fungal ICA mycotic aneurysm cases.Case Description A 76-year-old woman with rheumatoid arthritis, treated with etanercept and methotrexate, presented with a 2-week history of left temporal headaches. She was treated empirically for giant cell arteritis (GCA) with oral prednisone, which provided no symptom relief. She was subsequently hospitalized for a superficial temporal artery biopsy, which was negative for GCA. She returned 2 weeks later after experiencing a left thromboembolic ischemic stroke. She had an acute neurologic decline, and a head computed tomography scan showed diffuse subarachnoid hemorrhage from a ruptured left fusiform paraclinoid ICA aneurysm. She was taken emergently for a craniotomy for clip-wrapping of the aneurysm, but intraoperative ultrasound revealed poor flow in the left anterior cerebral circulation and a complete infarct of the left-sided anterior circulation. The family withdrew care and the patient died. Postmortem analysis demonstrated fungi consistent with Aspergillus invading the necrotic left ICA.Conclusions Although fungal mycotic aneurysms of the ICA are rare, their incidence may increase with the expanded use of immunosuppressive medications. Patients with rheumatoid arthritis who take potent immunosuppression regimens may be prime candidates for mycotic aneurysms because they often have two favoring conditions: atherosclerosis and immunosuppression. These ICA aneurysms carry a high mortality rate, so early diagnosis and aggressive therapy, potentially by endovascular trapping/vessel occlusion coupled with long-term antifungal therapy, is essential.
Keywords: TNF-α inhibitors; invasive fungal infections; infectious carotid aneurysms